Root water uptake modeling for unsaturated flow simulation and groundwater recharge assessment - Grinevskii S.O. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Московский государственный университет им. М. В. Ломоносова», 2011)
The comparison of two models of root water uptake in vadoze zone with different root distribution functions for groundwater infiltration recharge estimation was considered. On the base of transpiration process analysis and model sensitivity assessment the generalized parameters of root water uptake model were obtained for different landscape and soil conditions. Proper choice of root water uptake model and method of its parameter estimation allows to reduce errors of groundwater infiltration recharge estimation based on unsaturated flow modeling.
Keywords: ВОДНЫЙ БАЛАНС; ROOT WATER UPTAKE; ТРАНСПИРАЦИЯ; TRANSPIRATION; ЗОНА АЭРАЦИИ; VADOSE ZONE; ВЛАГОПЕРЕНОС; МОДЕЛИРОВАНИЕ; ИНФИЛЬТРАЦИОННОЕ ПИТАНИЕ; GROUNDWATER RECHARGE; UNSATURATED FLOW MODELING; INFILTRATION; 556.14:556.332.2:556.136:556.164